2016
DOI: 10.1111/cei.12828
|View full text |Cite
|
Sign up to set email alerts
|

Human leucocyte antigen class I-redirected anti-tumour CD4+ T cells require a higher T cell receptor binding affinity for optimal activity than CD8+ T cells

Abstract: SummaryCD4+ T helper cells are a valuable component of the immune response towards cancer. Unfortunately, natural tumour‐specific CD4+ T cells occur in low frequency, express relatively low‐affinity T cell receptors (TCRs) and show poor reactivity towards cognate antigen. In addition, the lack of human leucocyte antigen (HLA) class II expression on most cancers dictates that these cells are often unable to respond to tumour cells directly. These deficiencies can be overcome by transducing primary CD4+ T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Polyfunctionality is a highly desirable feature of potent CD8 þ T cells, well known in infections (17), but only recently described in cancer immunity (11,27). This feature is known to correlate with antigen-sensitivity and TCR affinity for cognate antigen (18,28). We showed that polyfunctional tumorreactive CD8 þ T cells accumulate in the peripheral blood of patients treated with TILs and that individual clonotypes within the TILs persist in patient peripheral blood 6 months after treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Polyfunctionality is a highly desirable feature of potent CD8 þ T cells, well known in infections (17), but only recently described in cancer immunity (11,27). This feature is known to correlate with antigen-sensitivity and TCR affinity for cognate antigen (18,28). We showed that polyfunctional tumorreactive CD8 þ T cells accumulate in the peripheral blood of patients treated with TILs and that individual clonotypes within the TILs persist in patient peripheral blood 6 months after treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Polyfunctionality is a desirable feature of potent CD8 þ T cells, well known in infections (29), but only recently described in cancer immunity (11,30). This feature is known to correlate with antigen sensitivity and TCR affinity for cognate antigen (31,32), antigen concentration (33), and, partially, differentiation status (34). We recently showed that polyfunctional T cells dominate the periphery after successful TIL therapy for cancer (35).…”
Section: Polyfunctional Characterization Of Tumor-reactive Cd8 þ T Cellsmentioning
confidence: 99%
“…T-cell receptor (TCR) ligation to a peptide presenting HLA molecule (pHLA) is critical to the effective activation of T-cells ( 20 , 21 ). The binding affinity between the TCR and core region of the peptide coupled with the half-life of peptide-TCR interaction collectively govern the downstream effector function ( 22 , 23 ). The TCR-pHLA binding affinity confers underlying signaling cascades leading to an increased demand for the extracellular glucose needed to produce biosynthetic intermediates for proliferation in addition to cellular ATP ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%